Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design. (February 2023) - Hassan, Sadaf Ul; Shafique, Sidra; Palvasha, Bushra Anees; Saeed, Muhammad Haris; Raza Naqvi, Syed Ali; Nadeem, Sohail; Irfan, Syed; Akhter, Toheed; Khan, Asim Laeeq; Nazir, Muhammad Shahid; Hussain, Murid; Park, Young-Kwon
Abstract: Mixed Matrix Membranes have gained significant attention over the past few years due to their diverse applications, unique hybrid inorganic filler and polymeric properties. In this article, the impregnation of nano-hybrid filler (polyoxometalates (∼POMs) encapsulated into the metal-organic framework (MOF) ∼ PMOF) on the polysulfone membrane (∼PSF) was done, resulting in a mix matrix membrane (∼PMOF@PSF). The developed structure was characterized by Fourier transform infrared (FT-IR), powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and transmission electron microscopes (TEM). The results confirmed that the nano-hybrid filler was successfully fabricated on the surface of PSF. Different loading ratios of nano-hybrid filler (5%, 10%, 20%, 30%, and 40%) were used for impregnation. The study's objective was to enhance catalytic performance using optimization curves designed using a three-level Box-Behnken Design (BBD) simulation. The photodegradation of Methylene Blue (∼MB) was studied against PMOF@PSF30% and was found to perform optimally when the concentration of catalyst, time of degradation, and temperature were 0.05–0.15 gm, 40–120 min, and 30–70 °C respectively. These experiments were replicated 15 times, and obtained results were further processed using a two-quadratic polynomial model to develop response surface methodology (RSM), which allowed for a functional relationship between the decolorization and experimental parameters. The optimal performance of the reaction mixture was calculated to be 0.15 gm for concentration, 70 °C for temperature, with an 80 min reaction time. Under these optimal conditions, the predicted decolorization of MB was 98.09%. Regression analysis with R 2  > 0.99 verified the fit of experimental results with predicted values. The PMOF@PSF PSF30% demonstrated excellent reusability as its dye degradation properties were significantly unaffected after ten cycles. Graphical abstract: Image 1 Highlights: Development of a Mixed Matrix Membrane (∼PMOF@PSF) by the impregnation of hybrid nano-filler on the polysulphone membrane. PMOF@PSF photocatalytic activity was tested against methylene blue and optimized using a Box-Behnken design (BBD). The optimal performance was found at; concentration (0.15 gm), temperature (70 °C), and reaction time (80min). The PMOF@PSF demonstrated great reusability as its dye degradation properties significantly affected after 10 cycles.